Zebrafish models in glioma research: advances in methodologies, mechanistic insights, and therapeutic frontiers - Tao, Runchao; Qu, Junying; Zhao, Jing; Wu, Baihui; Xu, Huaibiao; Yang, Liangwei; Qin, Hongru; Chen, Rongbing; Yang, Qinsi; Cheng, Yongwei; Wu, Wei; Sun, Da; et al. (Frontiers in Immunology, 2025)
Glioma is the most common primary malignant brain tumor, which faces great challenges in clinical treatment due to its high invasiveness and resistance to existing treatments. In recent years, the zebrafish model has gradually become an important tool for glioma research due to its advantages such as easy genetic manipulation, strong optical transparency, and suitability for high-throughput imaging and drug screening. This article systematically reviews the three main strategies for zebrafish glioma modeling - chemical mutagenesis, genetic engineering and xenotransplantation, and describes their research applications in tumorigenesis, invasion process and treatment response. At the same time, this article deeply analyzes the limitations of the zebrafish model in terms of temperature differences, delayed development of the blood-brain barrier and immature immune system, and introduces the cutting-edge progress in recent years in the fields of CRISPR-mediated immune regulation, construction of high-temperature resistant strains and development of humanized models. Through a comprehensive review of current research applications, key challenges and future development directions, this article emphasizes the potential value of the zebrafish model as an important supplement to the mammalian model in exploring the immune mechanism of glioma and developing innovative treatment strategies.